O papel da associação de hidroclorotiazida e treinamento físico no manejo da hipertensão e da lesão renal em ratas menopausadas - Neves, Pietra Petrica (2022)
Cardiovascular diseases are currently the main causes of mortality and morbidity worldwide. Blood pressure variability (BPV) has been associated with target organ damage, such as the kidneys. Pharmacotherapy associated with physical training is clinically recommended for blood pressure (BP) control in the management of SAH. Objective: To investigate the effects of combined physical training (CPT) associated with treatment with hydrochlorothiazide (HCT) on BPV and on renal morphofunctional, inflammatory and oxidative stress parameters. Method: 32 spontaneously hypertensive rats (SHR) were used, divided into 4 groups (n=8/group): sedentary oophorectomized (OS), sedentary oophorectomized treated with hydrochlorothiazide (OSH), trained oophorectomized (OT) and trained oophorectomized treated with hydrochlorothiazide (OTH). Oophorectomy was performed at baseline. After adapting to the treadmill and physical training ladder, the OS group continued with placebo treatment for 8 weeks, while the other groups received treatment with HCT (30mg/kg in drinking water) and/or combined physical training (CPT) (3 days /week, 40-60% of the maximum capacity obtained in treadmill and stair treadmill tests). After 8 weeks, we recorded the BP to analyze the BPV, inflammatory mediators and oxidative stress in renal tissue. Results: The OSH, OT and OTH groups had lower systolic pressure (SOH:189±13; TO:179±5; TOH:174±15 mmHg) when compared to the OS group (208±15 mmHg). There was an improvement in physical capacity in OT and OTH groups. The combination of therapies promoted a reduction in SBP variance. There was no difference between groups for plasma urea and proteinuria, but groups treated with HCT had lower levels of plasma creatinine, increased creatinine clearance and reduced glomeruli than the OS group. The results showed that the OS group showed a reduction in fields with an area of tubulointerstitial fibrosis of 0 - 25% and an increase in fields of 51 - 100% when compared to the other studied groups. On the other hand, the OTH group showed an increase in fields with alterations of 0 - 25% and a reduction in the number of fields in the ranges of 26 - 50% when compared to all other studied groups, in addition to a reduction in fields of 51-100% vs. the OS group. The OTH group showed an increase in the renal IL10/TNF-alpha ratio when compared to the other groups. There was a reduction in oxidized proteins in the trained groups and an increase in catalase activity in the OTH group (vs. OS). Conclusion: The results showed that the combination of hydrochlorothiazide and CPT is more effective than the drug alone in promoting BPV improvement, impacting on the improvement of the inflammatory and redox profile in renal tissue, promoting additional renal morphofunctional benefits increased creatinine clearance and of reduction on tubulointerstitial fibrosis in oophorectomized hypertensive rats.